Teacher’s reflections about the purport of master courses - Alevtina S. Robotova (Высшее образование в России)
The paper puts once again the question of the meaning of modern magistracy. By the example of the Master course “Spiritual and moral development” the author contemplates about the purposes and ways for upbringing the modern humanities scholars. Special attention is paid to the difficulties for magistrates and to a new situation for a magistracy teacher, and also to the pedagogical results, which encourage him and give a support.